Social vulnerability index-assessment for Iceland - Ströberg, Carl Andreas Fossick, 1985- (2018)
Although much attention has been given to urbanization and rural development issues in Iceland, their effect on communities vulnerability to environmental hazards has so far been given less attention. This study assesses the impact that urbanization in Iceland has on the socio-economic conditions that commonly affect the preparedness for, susceptibility to, and ability to recover from the possible impact of environmental hazards. The study applies a social vulnerability index-assessment to identify how a variety of socio-economic variables combine to produce different levels of social vulnerability in Icelandic municipalities. Six components, consisting in total of 17 socio-economic variables, were identified as either increasing or decreasing social vulnerability through different combinations across the country. Results indicate that that urbanization in Iceland has a larger scale effect of decreasing social vulnerability for a majority of its population which is urbanizing, while increasing it for the small minority that reside in municipalities suffering most from demographic and economic decline. Whereas demographic instability, unemployment, and/or a lack of permanent residents tended to increase social vulnerability the most, an unhealthy economic climate was a more common contributor across the country as a whole. A healthy economic climate and conditions on the housing market was identified as the strongest factors for lowering social vulnerability, mainly, but not exclusively in densely populated urban areas. Á meðan málefni er varða þéttbýlismyndun og dreifbýlisþróun á Íslandi hafa vakið talsverða eftirtekt þá hefur skort á umfjöllun um tengsl þeirra varðandi varnarleysi samfélaga gagnvart umhverfishættum. Þessi rannsókn metur þau áhrif sem borgarvæðing á Íslandi hefur á þær félags-hagfræðilegu aðstæður sem venjulega hafa áhrif á undirbúning, áhættu um og hvernig samfélög jafna sig eftir mögulegar umhverfishættur. Í rannsóknin er beitt mælikvarða á félagslegt varnarleysi til segja til um hvernig ...